Literature review on technology usage and emotional connection among children - Ismail, N.F. (IEEE Computer Society, 2017)
The aim of this research is to develop constructs for a measurement to assess children's emotional connection towards technology. The emerging technologies impact our way of livings in different ways regardless of age. If technology is properly used, it can make betterment to one's life, but if it is improperly used, it causes severity to human beings. The impact of technology that we may not realize is related to young adult especially underage children. The main problem identified is the excessive usage of technology can impact children negatively. It is a real life problem because firstly, parents have no idea what level of screen time is appropriate for children and secondly, the children's interaction with technology is inadequately control. The impact arises from the excessive usage of technology could be hindered if we could be informed about the severity of technology usage among children. Therefore the objective of this article is to define technology usage and emotional connection from reviewing literature. The technology being considered is mobile devices such as smartphones and tablet. Findings from the literature reviewed suggested that there is a relationship between technology use and emotional connection as spending too much time in front of screens could lead to an emotional dependency. © 2017 IEEE.